Multifrequency bioelectrical impedance estimates the distribution of body water - Cha, K; Chertow, G M; Gonzalez, J; Lazarus, J M; Wilmore, D W (Journal of applied physiology (1985), 1995)
Multifrequency bioelectrical impedance analysis was used to estimate the ratio of extracellular water (ECW) to total body water in subjects with end-stage renal disease. The body's resistance was measured at frequencies ranging from 1 kHz to 1 MHz. The impedance index (height2/resistance) determined at low frequency (5 kHz) correlated most closely with ECW (r = 0.886) using sodium bromide dilution as the standard of comparison. In contrast, the ratio of height squared to resistance determined at high frequency (500 kHz) correlated most closely with total body water (r = 0.974) using deuterium oxide dilution as the standard of comparison. The ratio of resistance at 500 kHz to resistance at 5 kHz was directly correlated (r = 0.767) with the ratio of ECW to total body water. Multifrequency bioelectrical impedance analysis may assist in the evaluation of body water distribution in endstage renal disease and other clinical disorders of fluid volume and/or distribution.